Millimeter-wave array enabled UAV-to-UAV communication technology - Zhenyu XIAO; Ke LIU; Lipeng ZHU (Tongxin xuebao, 2022)
As the application scope of unmanned aerial vehicle (UAV) expands and the tasks become more complicated, the demands for large bandwidth, high data rate and antijamming capability in UAV-to-UAV (V2V) communication grow rapidly.With abundant spectrum resource, millimeter-wave (mmWave) array communication has been one of the key technologies to support V2V communications.Focusing on the emerging field of mmWave array V2V communication, the difficulties and challenges in point-to-point communication and unmanned aerial vehicle ad-hoc network were analyzed.The problems and approaches for channel modeling, robust beamforming, secure communication in point-to-point communication and neighbor discovery, routing decisions, resource allocation, distributed deployment in unmanned aerial vehicle ad-hoc network were reviewed.Some valuable research directions were summarized to provide inspiration for future relevant research.